Parental Involvement Growth in Early Childhood Education: A Comparative Study in the Free State Province of South Africa - Chinedu Ifedi Okeke; Thomas Ogbeche Akobi (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study examined parental involvement in early childhood education at mobile ECD centres in the Free State province, South Africa, focusing on centres managed by Tshepang Educare Trust, Ntataise, and Lesedi Educare Association. A quantitative research approach with a descriptive survey design was used to gather data from 172 practitioners, selected through proportionate stratified random sampling. The sample included 11 practitioners from Lesedi Educare Association, 8 from Tshepang Educare Trust, and 153 from Ntataise. Data were collected using a 20-item structured questionnaire, validated by experts, with a reliability index of 0.79. Analysis was conducted using SPSS version 25, applying mean, standard deviation, t-tests, and one-way ANOVA. Findings revealed that parental involvement was highest at Ntataise, followed by Tshepang Educare Trust and Lesedi Educare Association, with an overall high level of involvement (cluster mean of 3.29). The most significant form of parental engagement was ensuring proper invitations for meetings. Meanwhile, the lowest score was for maintaining a sense of ownership by parents of the school. These results underscore the importance of support structures in fostering parental involvement.